Effect of simple vs. extended cholecystectomy on prognosis of T1b gallbladder cancer: a systematic review and meta-analysis - Gu, Hongpeng; Zhang, Guoqiang; Ma, Haijie; Yu, Ze (Frontiers in Surgery, 2025)
Background & aimsExtended cholecystectomy (EC) is recommended for T1b gallbladder cancer (GBC), but the optimal surgical procedure for T1b GBC remains controversial. This study aims to compare the prognosis of T1b GBC patients who underwent simple cholecystectomy (SC) vs. EC from a long-term survival perspective.MethodsWe performed a systematic search up to August 06, 2024, using MEDLINE (PubMed), EMBASE, Web of Science and Cochrane Library. The main outcomes were overall survival (OS) and disease-specific survival (DSS). We evaluated the quality of the studies included and the risk of bias, calculated the pooled hazard ratios (HRs) for OS and DSS and conducted the sensitivity analysis.ResultsA total of 8 retrospective studies involving 2,097 T1b GBC patients (SC = 1,263, EC = 408) were included. The pooled result of OS showed that the EC group had a significantly better OS than the SC group (pooled HR = 0.73; 95% CI = 0.59–0.89; P = 0.002). The pooled result of DSS indicated that EC significantly improved DSS of T1b GBC compared to SC (pooled HR = 0.47; 95% CI = 0.29–0.77; P = 0.003).ConclusionsEC should be chosen as the optimal surgical procedure for patients with T1b GBC from the standpoint of long-term postoperative survival. However, further analysis of more comprehensive studies will be necessary in the future to improve the quality of evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023449431, PROSPERO CRD42023449431.